أحكام الربح في عقود الاستثمار -المضاربة نمو>جا- - وهيبة, بوغزالة حمد (University of Eloued جامعة الوادي, 2019)
"ملخص البحث: تعالجهذهالدراسةموضوعأحكامالربحفيعقودالاستثمارالمضاربةنموذجا. لأن عقودالاستثمارتعتبرمنأهمالعقودالمتداولةحديثا،فقدحاولتمنخلالهذاالدراسة بيانمفهومالربحوبيانأهميتهوحكمهوضوابطه،كماعالجت فيهذهالدراسةمفهومالاستثماروضوابطهوأنواعهواشتملالمبحثالأخيرعلىدراسةالمضاربةمنحيثمفهومهاوبيانأحكامالربحفيهاالفاسدةمنهاوالصحيحة على السواء. " "AbSTRACT: This study deals with the subject of the provisions of profits in speculation investmet's contacts as a model. Investmet contracts are considered to be recent traded ones. In this study, we tried to explain the concept of profits, its imporatnce, its governance, and its controls. The last chapter included the study of the provisions of corrupt as well as valid profits. "
مذكرة ماستر تخصص معاملات مالية معاصرة
Keywords: أحكام الربح - الاستثمار - المضاربة; provisions of profits - contacts - speculation